2016
DOI: 10.1097/md.0000000000004180
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of macular edema without discontinuation of fingolimod in a patient with multiple sclerosis

Abstract: Introduction:Generally, fingolimod administration is simply discontinued when fingolimod-associated macular edema (ME) appears, and the majority of cases are said to recover spontaneously. However, to the best of our knowledge, this is the 1st report regarding improvement of ME without discontinuation of fingolimod administration.Case presentation:The patient was a 66-year-old woman with relapsing-remitting multiple sclerosis. She was started on treatment with fingolimod to prevent recurrence, after which she … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Our study found that FAME occurred mainly 3 m after the initiation of fingolimod, consistent with the phase III MS study and their extensions (14). However, a small proportion of patients develop late-onset ME (more than 12 months) (6,15,24,30,35), and blurred vision has also been reported as early as 24 h after initiation of the 0.5 mg dose (29). Patients with ME with diabetes or previous uveitis appear to develop it earlier.…”
Section: Discussionsupporting
confidence: 86%
“…Our study found that FAME occurred mainly 3 m after the initiation of fingolimod, consistent with the phase III MS study and their extensions (14). However, a small proportion of patients develop late-onset ME (more than 12 months) (6,15,24,30,35), and blurred vision has also been reported as early as 24 h after initiation of the 0.5 mg dose (29). Patients with ME with diabetes or previous uveitis appear to develop it earlier.…”
Section: Discussionsupporting
confidence: 86%
“…Options include topical anti-inflammatory agents; sub-Tenon or intravitreal corticosteroids; oral acetazolamide, observation with close follow-up, or drug discontinuation. [370][371][372][373][374][375][376][377][378] Baseline screening examination before starting fingolimod followed by regular examinations is recommended as CME might develop after several years. 379…”
Section: Managementmentioning
confidence: 99%
“…Incidence of FAME ranges from 0 to 2.08%; it occurs mainly during the first 3-4 months of therapy [13] and resolves spontaneously in the majority of patients after cessation of treatment. Oral administration of acetazolamide [14], non-steroidal anti-inflammatory drops [15] and intravitreal injection of steroid [16] have been also successfully used to treat macular oedema avoiding discontinuation of FTY [15][16][17].…”
Section: Introductionmentioning
confidence: 99%